The PPSQ: assessing parental, child, and partner’s playfulness in the preschool and early school years - Jean-François Bureau; Khachadour Bandk; Audrey-Ann Deneault; Jessica Turgeon; Harshita Seal; Patricia Brosseau-Liard (Frontiers in Psychology, 2023)
IntroductionDevelopmental research has traditionally focused on parenting behaviors such as nurturance and care, due to a focus on mothers’ behaviors. Other parenting dimensions such as parental playfulness (i.e., use of creativity, imagination, and humor during parent–child interactions) have comparatively received little attention. Although some measures tap into parents’ and children’s playfulness, these measures are limited. Indeed, they do not assess multiple domains of playfulness (i.e., both parents’ and the child’s playfulness) or focus on one specific setting such as children’s play with peers. Additionally, existing measures do not consider parents’ reactions to their partners’ playfulness. To address this gap, we created the Playful Parenting Style Questionnaire (PPSQ), which assesses three domains of playfulness: (a) parental domain, (b) child domain, and (c) partner domain. The current study is part of a validation effort of the PPSQ using a quantitative design. We aimed to explore the structure of the PPSQ by conducting an exploratory factor analysis (EFA) for each domain of playfulness; and assess the construct validity of the PPSQ factors by examining the association between factors and existing measures of playful parenting, child playfulness, and co-parenting.MethodThe sample includes 347 parents (294 mothers and 53 fathers) of preschool/school-age children (M = 5.10 years; 182 girls, 127 boys). Parents were mostly White (76%) and from a low socioeconomic risk background. Parents completed a series of online questionnaires including the PPSQ, 3 existing measures of parent playfulness (Parental Playfulness Questionnaire; Adult Playfulness Scale; Challenging Parenting Behavior Scale), 2 existing measures of child playfulness (Child Behavior Inventory; Children’s Playfulness Scale), a coparenting instrument (Co-parenting Relationship Scale), and sociodemographic information.ResultsThe EFA revealed 4 factors for parental playfulness, 1 factor for child playfulness, and 3 factors for partner’s playfulness. The construct validity analyses identified multiple associations indicating convergence with existing measures for the parent and partners domain but not the child factor.DiscussionThis study allowed for a better understanding of the playful dynamics that occur within a family.